Who Wrote the Book of Life? A History of the Genetic Code - Kay, Lily E. (Stanford University Press, 2000)
"Drawing on archives, published sources, and interviews, the author situates work on the genetic code (1953-1970) within the history of life science, the rise of communication technosciences (cybernetics, information theory, and computers), the intersection of molecular biology with cryptanalysis and linguistics, and the social history of postwar Europe and the United States."--Jacket.